It can be said (that): Lexical Bundles in English Extended Abstracts of Locally Published Turkish Research Articles - Fevzi Umut ÖZÇELİK; Betül BAL GEZEGİN (Dilbilim Araştırmaları Dergisi, 2025)
Building on existing literature on phraseology, this study explores how Turkish scholars employ lexical bundles in their extended abstracts. To this end, a corpus of the extended abstracts from five disciplines was collected. The structures and functions of the four-word lexical bundles identified in the extended abstracts were analyzed based on the previously structured two taxonomies (Biber et al., 1999; Hyland, 2008a). The analysis revealed 116 four- word lexical bundles. The findings indicate that, in contrast to previous studies using the same taxonomies, most of the identified lexical bundles in this study are structurally categorized as verb-constructed and functionally classified as text-oriented. We conclude with the potential benefits of this parallel lingual environment created by extended abstracts, which may act as a catalyst to overcome the possible linguistic challenges faced by English as an Additional Language scholars.